FAKTOR DESAIN CHATBOT (TONE, AVATAR, EMOSI, DAN INTERAKTIVITAS) TERHADAP PENGALAMAN DAN KEPUASAN PENGGUNA: SYSTEMATIC LITERATURE REVIEW - Nindy Viviva Asri; Devi Vara Pramudyta; Novita Fitriani (Jurnal Riset Sistem Informasi, 2026)
The advancement of artificial intelligence has accelerated the adoption of chatbots across various sectors, including customer service, education, healthcare, and e-commerce. However, chatbot effectiveness is influenced not only by technical performance, but also by the quality of interaction shaped through conversational design and user experience. In practice, many chatbots still fail to meet user expectations due to limited empathy, unnatural responses, and rigid interaction structures, which negatively affect user satisfaction and trust. This study aims to examine the role of chatbot design elements, including tone of voice, avatar, emotional expression, and interactivity, in shaping user experience and perceptions of digital interaction quality. The research employs a systematic literature review using a Grounded Theory framework. Data were analyzed through initial coding, conceptual categorization, and the identification of core themes derived from the selected literature. The findings indicate that these four design elements are interrelated and collectively contribute to more human-centered and meaningful chatbot interactions. Empathetic tone of voice, context-appropriate avatars, relevant emotional expressions, and responsive interactivity consistently enhance user engagement, trust, and satisfaction. This study contributes a synthesized conceptual framework that highlights the integrative role of chatbot design elements in shaping user experience, providing a theoretical reference for human-centered chatbot development.